Impact of Undernutrition on Tuberculosis Treatment Outcomes in India: A Multicenter, Prospective, Cohort Analysis. (25th November 2022) - Sinha, Pranay; Ponnuraja, Chinnaiyan; Gupte, Nikhil; Prakash Babu, Senbagavalli; Cox, Samyra R; Sarkar, Sonali; Mave, Vidya; Paradkar, Mandar; Cintron, Chelsie; Govindarajan, S; Kinikar, Aarti; Priya, Nadesan; et al.
Abstract: Background: Undernutrition is the leading risk factor for tuberculosis (TB) globally. Its impact on treatment outcomes is poorly defined. Methods: We conducted a prospective cohort analysis of adults with drug-sensitive pulmonary TB at 5 sites from 2015–2019. Using multivariable Poisson regression, we assessed associations between unfavorable outcomes and nutritional status based on body mass index (BMI) nutritional status at treatment initiation, BMI prior to TB disease, stunting, and stagnant or declining BMI after 2 months of TB treatment. Unfavorable outcome was defined as a composite of treatment failure, death, or relapse within 6 months of treatment completion. Results: Severe undernutrition (BMI <16 kg/m 2 ) at treatment initiation and severe undernutrition before the onset of TB disease were both associated with unfavorable outcomes (adjusted incidence rate ratio [aIRR], 2.05; 95% confidence interval [CI], 1.42–2.91 and aIRR, 2.20; 95% CI, 1.16–3.94, respectively). Additionally, lack of BMI increase after treatment initiation was associated with increased unfavorable outcomes (aIRR, 1.81; 95% CI, 1.27–2.61). Severe stunting (height-for-age z score <−3) was associated with unfavorable outcomes (aIRR, 1.52; 95% CI, 1.00–2.24). Severe undernutrition at treatment initiation and lack of BMI increase during treatment were associated with a 4- and 5-fold higher rate of death, respectively. Conclusions: Premorbid undernutrition, undernutrition at treatment initiation, lack of BMI increase after intensive therapy, and severe stunting are associated with unfavorable TB treatment outcomes. These data highlight the need to address this widely prevalent TB comorbidity. Nutritional assessment should be integrated into standard TB care. Abstract : Undernutrition is the leading risk factor for TB globally. This multicenter prospective cohort analysis shows that severe undernutrition at baseline or before TB disease, severe stunting, and lack of weight gain during intensive therapy are associated with unfavorable outcomes.